2008
DOI: 10.1007/s11481-008-9129-z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model System for Design of Biomaterials Based on Recombinant Analogs of Spider Silk Proteins

Abstract: Spider dragline silk possesses impressive mechanical and biochemical properties. It is synthesized by a couple of major ampullate glands in spiders and comprises of two major structural proteins--spidroins 1 and 2. The relationship between structure and mechanical properties of spider silk is not well understood. Here, we modeled the complete process of the spider silk assembly using two new recombinant analogs of spidroins 1 and 2. The artificial genes sequence of the hydrophobic core regions of spidroin 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 47 publications
(68 reference statements)
1
59
0
1
Order By: Relevance
“…The diameter of the electrospun Coll/PLLCL nanofibers ranged from 183 to 235 nm, which mimics the nanoscale dimensions of native ECM. It was reported that cells attach to and organize well around fibers with diameters smaller than the diameter of the cells [28]. Furthermore, fibrillar structure was found to promote cell attachment, proliferation and colony-forming capacity of stem cells in vitro in comparison with (non-fibrillar) tropocollagen layers [12].…”
Section: Discussionmentioning
confidence: 98%
“…The diameter of the electrospun Coll/PLLCL nanofibers ranged from 183 to 235 nm, which mimics the nanoscale dimensions of native ECM. It was reported that cells attach to and organize well around fibers with diameters smaller than the diameter of the cells [28]. Furthermore, fibrillar structure was found to promote cell attachment, proliferation and colony-forming capacity of stem cells in vitro in comparison with (non-fibrillar) tropocollagen layers [12].…”
Section: Discussionmentioning
confidence: 98%
“…Spider silk has come to focus as its extraordinary mechanical and biochemical properties [19] in materials cloning and expression, as well as mimicking these properties in polymeric systems [20]. Recombinant spider silk protein has been successfully applied for such biomedical materials as scaffolds for tissue engineering [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising as not even the respinning of dissolved native spider silk results in fibres that match native silk [94,95]. For recombinant spidroins that do not self-assemble spontaneously, different methods to convert them into fibres have been used, such as wet spinning [9,53,62,70,79,86,96,97], hand drawing [82,96], spinning though microfluidic devices [83] and electrospinning [56,59,66,86,98]. A few recombinant spidroins that generate fibres stable and long enough to allow mechanical testing have been reported [11,70,86,92,93,96].…”
Section: Recombinant Spidroin Productionmentioning
confidence: 99%